Business Architecture Strategy and Platform-Based Ecosystems - Park, Young Won (Springer Singapore, 2018)
This book provides a framework and real case analyses concerning business architecture strategy and platform-based ecosystems. Firstly, the book introduces a framework of business architecture strategy and suggests an engineering process that employs a business architecture analysis system in which the various business best-practices information technology (IT) tools are integrated into an interface. More specifically, this architecture analysis provides the means to realize two essential features: a strategy that allows global firms to sense changing market needs, and a tool that combines mechanical engineering with electronics and software IT tools. Secondly, the book discusses platform-based ecosystems. Crucial issues for today's firms are associated with value creation through their platform and ecosystem framework. With a major emphasis on modular product architecture, US firms have focused heavily on platform development in modular industries. Their base is operation system (OS) software, so that IT firms in general focus on software capabilities-and digital control in particular. In contrast, the advantage for Japanese firms is not digital but analog control. Without any drastic changes in their industry practices, Japanese firms are likely to sustain their analog platform advantage. The book subsequently puts forward a holistic view through the connection of business architecture strategy and platform-based ecosystems. The theoretical framework and case illustrations are especially useful to firms involved in a variety of industries that must respond to the turbulent environmental changes of the digital era. Most of the cases target not only Japanese firms but also many other global firms. Readers are systematically shown how to balance technological competence and customer competence by using the framework of business architecture strategy and platform-based ecosystems.